Thermal Effect of Hollow Spheres in a Filtration Combustion Process - Bubnovich, V (Elsevier Ltd, 2021)
Filtration combustion, or porous media combustion, deals with the partial or total oxidation of a fuel in presence of a solid phase, achieving a more dynamic heat transfer process than conventional technologies. The thermal performance of the solid media has a direct effect on the reaction process, and commonly features a packed bed structure composed of solid spheres. The main objective of this manuscript is to investigate the thermal effect of hollow spheres as an inert solid medium in a filtration combustion process. A heat transfer analysis was developed considering the internal radiation of the hollow spheres and its density reduction in comparison with solid spheres. Then a one-dimensional model based on a two temperatures (gas and solid) approximation was presented using a one-step combustion chemistry for lean methane-air mixtures. Numerical and experimental results with hollow spheres as packed bed are in good agreement and demonstrate higher combustion wave temperatures and propagation rates than solid spheres. Upstream and downstream wave propagations were observed in the range of air–fuel ratios studied. It is shown that hollow spheres as packed bed is a good option for new designs of porous media burners. © 2021 Elsevier Ltd